2001
DOI: 10.1103/physreve.63.026408
|View full text |Cite
|
Sign up to set email alerts
|

Experimental verification of semiclassical and RPA calculations of the static conductivity in moderately nonideal plasmas

Abstract: We present an experimental verification of the semiclassical theory for static conductivity calculations in the case of moderately nonideal plasmas. Such plasmas are produced in linear flashlamps filled with pure helium and are characterized by on axis electron densities in the range 2x10(17)-1.7x10(18) cm(-3) and temperatures (2-3)x10(4) K. Precise measurements of the discharge electrical parameters have been carried out and in each case the impedance of the plasma was compared with the calculated value using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 8 publications
2
18
0
Order By: Relevance
“…Finally, comparing of the expressions (4.4), (4.5) and (4.6) for the potentials Φ (i,e) (r) with the expression (A3) for DH solutions Φ (i,e) D (r) shows that in two-component case the principal difference between these solutions there is not only inside the probe particle self-spheres, but also in the rest of space. Namely, out of these self-spheres Φ This fact justifies the usage in [7,8,9,10] the constants which are close to κ i and κ e instead of DH constants.…”
Section: What One Should Do In Order To Avoid Non-physicality Of Dsupporting
confidence: 53%
“…Finally, comparing of the expressions (4.4), (4.5) and (4.6) for the potentials Φ (i,e) (r) with the expression (A3) for DH solutions Φ (i,e) D (r) shows that in two-component case the principal difference between these solutions there is not only inside the probe particle self-spheres, but also in the rest of space. Namely, out of these self-spheres Φ This fact justifies the usage in [7,8,9,10] the constants which are close to κ i and κ e instead of DH constants.…”
Section: What One Should Do In Order To Avoid Non-physicality Of Dsupporting
confidence: 53%
“…It is important that the SC method gives practically the same results as the RPA method in a wider region of the electron densities around the value of N e = 10 17 cm −3 . The SC method was tested from this aspect in Vitel et al (2001), where it was experimentally verified through comparison with the results from Spitzer (1962) and Kurilenkov (1984), just for the helium plasmas.…”
Section: Theorymentioning
confidence: 99%
“…One of the most frequently used approximations for consideration of transport properties of different plasmas is the approximation of ‘fully ionized plasma’ (Spitzer 1962; Radke et al 1976; Adamyan et al 1980; Kurilenkov 1984; Ropke & Redmer 1989; Djuric et al 1991; Nurekenov et al 1997; Zaika, Mulenko & Khomkin 2000; Esser, Redmer & Ropke 2003). It was shown that the electrical conductivity of fully ionized plasmas can be successfully calculated using the modified random‐phase approximation (RPA) (Djuric et al 1991; Adamyan et al 1994a,b) in the region of strong and moderate non‐ideality, while the weakly non‐ideal plasmas were successfully treated within the semiclassical approximation (SC) (Mihajlov et al 1993; Vitel et al 2001). In practice, even the plasmas with a significant neutral component are treated as fully ionized in order to simplify the considered problems (Ropke & Redmer 1989; Esser & Ropke 1998; Zaika et al 2000; Esser et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Since the same quantity τ(E) is used in the expressions (1-3) for σ(ω) just the good understanding of the static conductivity σ 0 as a function of n e and T has a very important role in defining the strongly coupled plasma dynamic conductivity. Because of this fact our research was started in (see [14]) in the region of the plasma electron density n e ≤ 10 19 cm −3 , where the basic method of the determination of the σ 0 from [11,13] was experimentally verified [18]. Accordingly to [11,13], the relaxation time τ(E) is defined in the self-consistent approximation by the following relations:…”
Section: Basic Equationsmentioning
confidence: 99%